Pakistani Couples: Different Productive and Reproductive Realities? (The Pakistan Development Review, 2000)
Gender systems depict several dimensions of the relations between men and women across different social settings. Mason (1995) has described the complexity of gender systems that encompass concepts such as women’s standing, empowerment, the sexual division of spheres and the rather widely used concept of women’s status. Gender systems in Pakistan are posited to be unequal in favour of men, because of strong patriarchal systems, which ordain that men and older persons make all major decisions. As a result, women’s status is argued to be low in most dimensions: poor educational attainment, few economic opportunities apart from family based employment which is largely unpaid and the virtual seclusion of women from the public spheres of life especially those involving financial transactions. Spheres of life are quite separate with men having the primary responsibility of breadwinning and women to be primarily responsible for within household routine chores such as those involving cleaning, cooking, animal care and child care.